2010
DOI: 10.1016/j.brainres.2010.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of inflammatory markers in brain after hemorrhagic stroke in humans: A postmortem study

Abstract: This histopathologic case-control study was designed to characterize the dynamic changes in protein expression of nuclear factor-kappa B (NF-κB)/p65 subunit, macrophage inflammatory protein-2 (MIP-2), and matrix metalloproteinase-9 (MMP-9) in postmortem brains of patients with and without intracerebral hemorrhage (ICH). Thirty-six human brains from patients with ICH and six control brains were included in this study. We found that expression levels of NF-κB/p65, MIP-2, and MMP-9 were each upregulated on the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 30 publications
2
50
1
Order By: Relevance
“…Activated microglia and astrocytes and infiltrating macrophages are major inflammatory cells that contribute to secondary brain damage (e.g., brain oedema) after ICH1025. Our histologic data showed that microglia/macrophage activation peaked in the perilesional region on day 3 and then decreased with time.…”
Section: Discussionmentioning
confidence: 58%
“…Activated microglia and astrocytes and infiltrating macrophages are major inflammatory cells that contribute to secondary brain damage (e.g., brain oedema) after ICH1025. Our histologic data showed that microglia/macrophage activation peaked in the perilesional region on day 3 and then decreased with time.…”
Section: Discussionmentioning
confidence: 58%
“…Wu et al [46] confirmed the upregulation of MMP-9 in spontaneous ICH up to 5 days after hemorrhage onset. Additionally, NF-ĸB, p65 and macrophage inflammatory protein-2 were overexpressed, showing predominance at the hematoma site.…”
Section: Mmps and Human Spontaneous Ichmentioning
confidence: 59%
“…Wu et al [46] investigated the timing of secondary brain damage in patients with spontaneous ICH who underwent hematoma evacuation. Apart from increased levels of MMP-9, they observed overexpression of caspase-3 and proliferation of terminal uridine nick-end labeling-positive cells as early as 6 h after spontaneous ICH onset with the tendency to progression up to 24 h, limited by the duration of the observation.…”
Section: Mmps and Human Spontaneous Ichmentioning
confidence: 99%
“…It causes perihematomal edema, elevations in intracranial pressure, and neurologic deficits (Keep, et al, 2014). Hematoma formation, expansion, and mass effect cause the primary damage, whereas inflammatory response and oxidative stress contribute to the progression of secondary injury (Wang, 2010, Wu, et al, 2010). Because outcomes are poor, it is worth exploring approaches that can ameliorate the detrimental effects of neuroinflammation and improve functional recovery after ICH.…”
Section: Introductionmentioning
confidence: 99%